MORPHOFUNCTIONAL BASIS OF THE FORMATION OF CARDIAC OUTPUT - Zakharova, V.P.; Balabai, A.A.; Trembovetskaya, E.M.; Rudenko, E.V.; Rudenko, K.V.; Stechenko L.О. (World of Medicine and Biology, 2022)
The article is devoted to the study of the morphological basis of the formation of systolic blood ejection from the left ventricle into the systemic circulation. The myocardium is a continuous syncytium-like structure with multidirectional muscle fibers; however, different segments of the left ventricle during systole are allowing the myocardium to move along a certain trajectory in the absence of fulcrums. The mechanisms of myocardial movement in a certain direction remain unknown. The aim of our study was to study the morphological basis of the formation of systolic blood flow from the left ventricle into the great circle of blood circulation. Macroscopic, microscopic methods and speckle-tracking echocardiography were used in the study. The results of our study showed that the compact myocardium of the upper segments of the left ventricle of the heart is formed by connecting the strands of muscle fibers that change direction from “clockwise” to “counterclockwise”. The vector of movement of each segment of the myocardium depends on the direction of its muscle fibers and the sequence of contractions. The trabeculae contract first and are the fulcrum for compact myocardial cardiomyocytes, which determines the direction of movement of each segment of the left ventricular myocardium. Changes in myocardial architecture, as well as abnormal cardiomyocyte contractions, may lead to decreased stroke volume with symptoms of heart failure, which should be considered when making a diagnosis.